Consumption Pattern and Quality Characteristics of Tandoor / Tikka Type of Chicken Meat Product - Sen, A.R.; Reddy, G.V. Bhaskar; kumar, M. Mutu; Naveena , B.M.; A.S., Nithin; Naveena , B.M.; A.S., Nithin (Journal of Meat Science, 2019)
The present study was envisaged to assess the consumption pattern and influence of different cooking methods on quality characteristics of tandoor/tikka type of chicken meat product. A total of 112 consumers at 8 restaurants throughout Hyderabad were surveyed for consumption pattern of tandoor type muscle food based products. Most of the consumers prefer such type of product prepared from mutton. However, 43.14 % of consumers prefer chicken based and 6.86% of consumers prefer fish products. Amongst the products surveyed, 31 % consumers are preferring tandoor type of product, whereas 10% consumers mostly like tikka/kebabs type of products. The 70 % of total consumers take these types of products twice in a week. The 42.50 % of consumers are taking more than 200 gm of such products at a time. Cooking methods significantly (P<0.05) influenced by the both physico-chemical and sensory attributes of chicken tikka. Cooking yield (%) was significantly (P<0.05) more in oven cooked tikka as compared to barbecue and gas tanoor. The shear force value was more (27.43 N) in barbecued chicken tikka thant the product cooked in other two methods. Chicken tikka cooked in hot air oven method recorded more moisture and less fat content than other cooking methods. Colour, taste, mouth coating and overall palatability scores was rated higher in gas tandoor cooked product. Chicken tikka cooked in hot air oven rated superior tenderness and juiciness scores compared to other cooking methods. Based on this study, it can be concluded that alternatively chicken tikka can be produced in hot air oven, rather than open flame/tandoor oven with hither yield and superior tenderness and juiciness scores.